Desenvolvimento de uma estrutura robótica atuada por cabos para reabilitação/recuperação dos movimentos do ombro humano - Nunes, Wilgo Moreira (2012)
The robots have been used in many different areas, not only in industry. Studies with robots applied in human rehabilitation are developed to a greater well-being of the patient, for these tasks can be more efficient in performing these exercises than humans, because they can usually record information such as position, trajectory, power, speed and exploit the engine performance during movements to guide the limb of the patient. Thus, robots actuated by parallel cables have attracted researchers\' attention because of a number of benefits that make them suitable for rehabilitation purposes as workspace larger than the conventional parallel structures that can be adapted to different patients and therapies; easy assembly and disassembly mechanical structure, can be transported, the main advantage is the acceptance of patients already adapted therapies using cables. Thus, this work aims to build a parallel robotic structure actuated by cables toward the upper limb rehabilitation with emphasis on the shoulder. To achieve the goal of this dissertation, it is first carried out the study of existing structures for robotic rehabilitation of upper limb. After the upper limb is presented with its main movements and amplitudes. Following is presented the proposed structure and its mathematical modeling. The study of the workspace of the proposed structure is performed in accordance with movements of the human shoulder. Finally, is presented the prototype of CaMaReS (Cable Manipulator for Rehabilitation of Shoulder), graphical and numerical simulations and experimental tests performed.